2022
DOI: 10.3390/jcm11051279
|View full text |Cite
|
Sign up to set email alerts
|

QRS Narrowing Following CRT Implantation: Predictors, Dynamics, and Association with Improved Long-Term Outcome

Abstract: Background: Heart failure (HF) patients with wide QRS often benefit from cardiac resynchronization therapy (CRT), although QRS narrowing does not always occur. The current study investigates the incidence and predictors for QRS narrowing following CRT and its long-term impact on clinical outcomes. Methods: Among individuals undergoing clinically indicated CRT, pre-and post-implantation electrocardiographs were meticulously analyzed for QRS duration change. All-cause mortality and the composite of mortality and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 31 publications
1
5
1
Order By: Relevance
“…The short-survival group tended to have a reduced QRS width at 1 year after CRT-D implantation. It has been reported that a shortening of the QRS width by more than 20 ms after CRT implantation improved the long-term prognosis, 21 but the proportion of underlying cardiac disease was different from the present study, which had less ischemic heart disease. However, a paired T test showed that there was no significant difference between the changes before and after CRT-D implantation in both the short-survival group (p = .11) and the long-survival group (p = .33).…”
Section: Predictors Of Long-term Survival In the Present Studycontrasting
confidence: 87%
“…The short-survival group tended to have a reduced QRS width at 1 year after CRT-D implantation. It has been reported that a shortening of the QRS width by more than 20 ms after CRT implantation improved the long-term prognosis, 21 but the proportion of underlying cardiac disease was different from the present study, which had less ischemic heart disease. However, a paired T test showed that there was no significant difference between the changes before and after CRT-D implantation in both the short-survival group (p = .11) and the long-survival group (p = .33).…”
Section: Predictors Of Long-term Survival In the Present Studycontrasting
confidence: 87%
“…35 QRS duration >150 msec, especially with LBBB, is one of the main indications for implanting CRT in heart failure patients along with left ventricular EF and NYHA functional class, with its prognostication on a long-term response of CRT. 36 Our study showed that CRT could shorten QRS duration in patients with CHD with a mean QRS duration decrease up to 28.7 msec, which implies that CRT would probably mitigate dyssynchrony in ventricular contraction. Further, our study showed that the EF after implant CRT also increased (mean difference 11.8%).…”
Section: Chd Is the Most Common Embryonic Defect In Neonates Accountingmentioning
confidence: 52%
“…It has been shown that QRS width reduction after BiV implantation is associated with favourable long-term outcomes. [11] Average shortening of QRS and shortening of equivalent dipole lengths were similar in both groups. However, there was a significant difference in the shift of trajectory orientations.…”
Section: Discussionmentioning
confidence: 76%